Identification Osteogenic Signaling Pathways Following Mechanical Stimulation: A Systematic Review - Nokhbatolfoghahaei, Hanieh; Rad, Maryam R.; Paknejad, Zahrasadat; Ardeshirylajimi, Abdolreza; Khojasteh, Arash (Current Stem Cell Research & Therapy, 2022)
Introduction: It has been shown that mechanical forces can induce or promote osteogenic differentiation as well as remodeling of the new created bone tissues. To apply this characteristic in bone tissue engineering, it is important to know which mechanical stimuli through which signaling pathway has a more significant impact on osteogenesis. Methods: In this systematic study, an electronic search was conducted using PubMed and Google Scholar databases. This study has been prepared and organized according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Included studies were first categorized according to the in vivo and in vitro studies. Results: Six types of mechanical stresses were used in these articles and the most commonly used mechanical force and cell source were tension and bone marrow-derived mesenchymal stem cells (BMMSCs), respectively. These forces were able to trigger twelve signaling pathways in which Wnt pathway was so prominent. Conclusion: 1) Although specific signaling pathways are induced through specific mechanical forces, Wnt signaling pathways are predominantly activated by almost all types of force/stimulation, 2) All signaling pathways regulate expression of RUNX2, which is known as a master regulator of osteogenesis, 3) In Tension force, the mode of force administration, i.e, continuous or noncontinuous tension is more important than the percentage of elongation.
Keywords: osteogenic differentiation